The use of blastocysts developing from nonpronuclear and monopronuclear zygotes can be considered in PGT-SR: a retrospective cohort study - Jingzhen Wang; Hongqiang Xie; Yang Zou; Ming Gao; Lijuan Wang; Xiaowei Liu; Se-Xin Huang; Junhao Yan; Yuan Gao (BMC Pregnancy and Childbirth)
Abstract Background While zygotes lacking pronuclei (0PN) or exhibiting a single pronucleus (1PN) may theoretically yield diploid embryos with developmental potential, current clinical protocols predominantly exclude these embryos from use. In the population undergoing preimplantation genetic testing for structural rearrangements (PGT-SR), there is a high rate of chromosomal aneuploidy abnormalities and needs a large number of embryos to obtain euploid embryos, so we will explore whether 0PN and 1PN embryos can be an option for them. Methods This retrospective analysis examined pronuclear development in 4,868 zygotes derived from 4,902 injected metaphase II (MII) oocytes across 422 assisted reproductive cycles. In a subset of 54 cycles (12.8%), preimplantation genetic testing for structural rearrangements (PGT-SR) was implemented for blastocysts originating from 0PN and 1PN embryos that progressed to Day 5/6 development stage prior to vitrification. Comprehensive genomic haplotyping was performed on 343 embryos within this subgroup, including 33 0PN-derived, 36 1PN-derived, and 274 conventional 2PN-derived specimens. The investigation’s primary endpoint focused on neonatal survival outcomes, while secondary assessments evaluated both embryo transfer suitability and chromosomal normality rates. Results Compared to 2PN embryos, the proportion of 0PN and 1PN embryos developing into blastocysts is significantly lower (5.41%, 21.56% vs. 56.51%, p-value < 0.001); the euploid rate of 0PN blastocysts is not statistically different from that of 2PN blastocysts (18.18% vs. 33.21%, p-value = 0.111), but significantly lower for 1PN blastocysts (11.11% vs. 33.21%, p-value = 0.004). In 54 cycles involving 0PN and 1PN blastocysts, the inclusion of 0PN and 1PN embryos resulted in an increase in the number of frozen embryos (5.81 ± 3.55 vs. 7.09 ± 3.52, p-value = 0.063), transferable embryos (1.59 ± 1.25 vs. 1.78 ± 1.30, p-value = 0.452), embryos transferred (0.98 ± 0.76 vs. 1.07 ± 0.75, p-value = 0.526), and patients undergoing transfer (74.07% vs. 79.63%, p-value = 0.494), although these changes were not statistically significant. The five 0PN and 1PN embryos transferred resulted in three live births, which was not a significant increase (56.36% vs. 56.67%, p-value = 0.974). Conclusion Chromosome abnormalities did not increase the occurrence of abnormal fertilization. There were already a large number of embryos in the PGT-SR population, and routine inclusion of 0PN and 1PN embryos in the PGT-SR cycle is not recommended in this study. Priority should be given to the transfer of 2PN embryos. If a couple receives fewer than three 2PN embryos, or no 2PN embryos at all, it may be considered to include 0PN and 1PN embryos, with preference given to the use of 0PN. Furthermore, genome-wide ploidy and haplotyping are recommended for detection, and aneuploid and ploidy abnormalities are excluded.